Optimizing Investment Portfolio Selection Using Fuzzy Linear Programming: An Applied Study: تحسين اختيار المحفظة الاستثمارية باستخدام البرمجة الخطية الضبابية (Journal of Humanitarian and Applied Sciences, 2026)
In this paper examines investment portfolio problem under uncertainty using fuzzy linear programming.  Risk and returns are type of fuzzy numbers, and the portfolio problem of fuzzy number is transformed into a deterministic form based on a select -cut. A numerical example is used to study the impact of the -cut of investment decisions. Then the results prove that the proposed of fuzzy model offers greater suppleness than traditional approaches and enhances decision maker.
Keywords: linear programming problem; Investment Portfolio; fuzzy numbers; α -cut